Pembagian Harta Warisan dalam Perspektif Hukum Islam, Hukum Adat, dan Hukum Perdata di Indonesia - Indra Sakti; Nursania Dasopang (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This paradigm of Indonesian Islamic inheritance law is institutionalized in the Compilation of Islamic Law (KHI), which was enacted based on Presidential Instruction (Inpres) No. 1 of 1991. The provisions regarding inheritance are determined by Allah through His revelation in the Qur'an, which clearly articulates its intent and purpose. Various aspects still require clarification, both affirmative and detailed, as conveyed by the Prophet Muhammad (SAW) through his hadiths. Nevertheless, its application has sparked ongoing debate among Islamic legal scholars, which has been formulated into normative teachings. Inheritance law according to Islamic law is part of family law (al-Ahwalus Syahsiyah). This knowledge is very important to learn so that in the distribution of inheritance, there are no mistakes and it can be carried out as fairly as possible, because by studying Islamic inheritance law for Muslims, they will be able to fulfill their rights regarding inheritance after the death of the muwarris (decedent) and deliver it to the heirs who are entitled to receive it. Islamic inheritance law is a set of rules that governs the transfer of assets from a deceased person to their heirs. This means determining who the heirs are, the share of each heir, and determining the portion of the estate and inheritance given to the heirs.